An MDO concept for large civil airliner wings - Gantois, K. (Cranfield University, 1998)
This thesis investigates the application of Multi-Disciplinary Design, Anal- ysis and Optimisation to the design of a large civil airliner, similar in size as the future A3XX. For the first time structural optimisation, manufacturing cost and aerodynamic effects are simultaneously integrated within a realistic, complex aircraft design problem: the wing box of such a large airliner. A novel multi-level system was developed to incorporate structural effects and manufacturing cost: mass is treated at a top-level while costs are treated at a structural sub-level. It allows a designer to study cost changes with respect to design changes and the interaction of cost with other disciplines such as structures and aerodynamics. The flexibility of the system allows companies to import their own results or cost data and to perform cost studies based on historical data or highly novel processes. Structural optimisation of the wing box using MSc/NASTRAN and STARS, the development of a metal and composite cost model and the overall MDO methodology are being discussed.